Author productivity analysis in Q1 of authors in journal library and information science Q1 journals using with Lotka’s Law - Nasya Meilia Pratiwi; Cecep Ibrahim; Nisya Ula Alkarimah; Zalika Naila Arifah; Thufailah Hamida Jatmik; Afini Mutiara; Amelia Fatimah Azzahra; Sherin Wiryani Putri; Danang Dwijo Kangko; Rina Astarika; Jopang Jopang (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. The purpose of this study is to use Lotka's law to determine the pattern of author output in the field of Library Science in the Library Science Journal Q1 indexed by Scopus. Data Collection Methods. The quantitative descriptive method was conducted, with a bibliometric approach to explore aspects of scientific articles. Data Analysis. The research data was acquired from the Scopus International Journal, which can be viewed at www.scopus.com from 2018 to 2022, with article types. Results and Discussion. The research results found that the number of library science journals indexed by Scopus Q1 was 61. Based on the analysis of Lotka’s law calculations, it is found that the value of C is 0,518 and the value of n was 1,717. The productivity equation for SCOPUS-indexed authors in Library Science journals for 2018–2022 was 0,518, which results in the number of author contributions in publishing one article being 51,84%. In addition, the results of the analysis show that Dmax was 0.280 with a critical value of 0,009. Conclusion. These findings indicate that Dmax is bigger than the crucial value and it does not follow Lotka's law.